La nutrición infantil y sus efectos en el desarrollo físico-intelectual de los niños y niñas del quinto año de educación general básica paralelo B de la Unidad Educativa Rafael Vásconez Gómez en el período lectivo 2016-2017 - Salguero Vivanco, Rocío Elizabeth (2017)
The deficient child nutrition and its effects on the physical and intellectual development of the children of the fifth year of Basic General Basic Education "B" of the Educational Unit "Rafael Vásconez Gómez", belonging to the La Maná parish, La Maná, Province of Cotopaxi; Born with the purpose of improving physical-intellectual development; A diagnosis of the quality of nutrition was made through surveys, which allowed to know a high percentage of the students in study who attend the Educational Unit without having breakfast, a factor that impairs the physical and intellectual development. It is evident that the population is in a situation of food and nutritional insecurity impacting growth in children, increasing prevalence of overweight and malnutrition, in addition to inadequate eating habits, distribution of the economic resource in the purchase of food, lack of knowledge And practices in food. In addition, the institution has not implemented strategies that improve nutrition; but rather has spread the consumption of goodies; for these shortcomings the design of a nutritional leaflet was considered and it is socialized by means of trainings directed to the parents and the teacher. It offers the possibility of receiving a Nutrition Education for food consumption, the same that contains topics on the pyramid of child nutrition, hygiene in food handling, eating habits and a recipe of nutritious meals; Through workshops and with the joint support of the educational institution and the parents, it has been possible to significantly increase the food quality of the students, thus promoting an adequate physical and intellectual development, which in turn allows to improve the academic performance of Children.